Preliminares (2016)
Este documento contiene en texto completo el articulo Preliminares publicado en "Universidad & Empresa" Journal; Vol. 18, Núm. 31 (2016): (julio-diciembre,0); 1-7;Universidad & Empresa; Vol. 18, Núm. 31 (2016): (julio-diciembre,0); 1-7;2145-4558;0124-4639;10.12804/rev.univ.empresa.31.2016